Do early life cognitive ability and self-regulation skills explain socio-economic inequalities in academic achievement? An effect decomposition analysis in UK and Australian cohorts - Pearce, Anna (Pergamon, 2016)
Socio-economic inequalities in academic achievement emerge early in life and are observed across the globe. Cognitive ability and “non-cognitive” attributes (such as self-regulation) are the focus of many early years’ interventions. Despite this, little research has compared the contributions of early cognitive and self-regulation abilities as separate pathways to inequalities in academic achievement. We examined this in two nationally representative cohorts in the UK (Millennium Cohort Study, n = 11,168; 61% original cohort) and Australia (LSAC, n = 3028; 59% original cohort).